Пути развития института ареста морского судна в Украине после присое динения к Международной конвенции об унификации некоторых правил, касающихся ареста морских судов от 10.05.1952 г. - Картузов, Михайло Юрійович; Картузов, Михаил Юрьевич; Kartuzov, Mikhail (Одеса : Юрид. л-ра, 2012)
The article reviews the novels of the current legislation of Ukraine, which regulates the issues of the arrest of the sea-going ships. It reviews the peculiarities of the international practice of the arrest of the sea-going ships and practice of the developed countries in this area. The author makes the proposals of improving of the current commercial procedural legislation of Ukraine, which regulates the issues of arrest of the sea-going ships.
Картузов М. Ю. Пути развития института ареста морского судна в Украине после присое динения к Международной конвенции об унификации некоторых правил, касающихся ареста морских судов от 10.05.1952 г. / М. Ю. Картузов // Актуальні проблеми держави і права : зб. наук. пр. / редкол.: С. В. Ківалов (голов. ред.), В. М. Дрьомін (заст. голов. ред.), Ю .П. Аленін [та ін.] ;МОНмолодьспорт України, НУ «ОЮА». – Одеса : Юрид. л-ра, 2012. – Вип. 67. - С. 331-340.
Keywords: арест морского судна; морское требование; обеспечение морского требования; предупредительные меры; встречное обеспечение; арешт морського судна; морська вимога; забезпечення морської вимоги; запобіжні заходи; зустрічне забезпечення; arrest of Sea-going Ships; maritime claim; security of maritime claim; preventive measures; counter-assurance